Enhancing cannabidiol bioaccessibility using ionic liquid as emulsifier to produce nanosystems: Characterization of structures, cytotoxicity assessment, and in vitro digestion - Vardanega, Renata (2024)
The emulsifying potential of a biocompatible ionic liquid (IL) to produce lipid-based nanosystems developed to enhance the bioaccessibility of cannabidiol (CBD) was investigated. The IL (cholinium oleate) was evaluated at concentrations of 1 % and 2 % to produce nanoemulsions (NE-IL) and nanostructured lipid carriers (NLC-IL) loaded with CBD. The IL concentration of 1 % demonstrated to be sufficient to produce both NE-IL and NLC-IL with excellent stability properties, entrapment efficiency superior to 99 %, and CBD retention rate of 100 % during the storage period evaluated (i.e. 28 days at 25 °C). The in vitro digestion evaluation demonstrated that the NLC-IL provided a higher stability to the CBD, while the NE-IL improved the CBD bioaccessibility, which was mainly related to the composition of the lipid matrices used to obtain each nanosystem. Finally, it was observed that the CBD cytotoxicity was reduced when the compound was entrapped into both nanosystems.